Effect of social media influencers on brand preferences through trust: Moderating role of emotional attachment - Khansa Zaman; Sajjad Nawaz Khan; Muhhamad Abbas; Amani AbdAlatti (Innovative Marketing)
Social media influencers have gained immense attention in recent times due to increased use in the cosmetics industry. Trust and emotional attachment play a vital role between influencers and followers. The aim of this study is to investigate the impact of social media influencers’ characteristics on predicting intention to buy the recommended beauty brands through trust and a moderating role of emotional attachment with influencers. A sample size of 342 respondents from Pakistan was used to empirically test the hypothesized relationships. The respondents were social media users who follow renowned celebrities on various social media platforms and buy beauty products based on their recommendations. Thus, a purposive sampling technique was employed for data collection using online and in-person data collection methods. Quantitative techniques of regression and process models were used for data analysis. The findings show that characteristics of social media influencers, such as credibility and trustworthiness, have a significant positive impact (β = 0.521, p < .05) on the intention to buy cosmetic products from a particular brand. Likewise, emotional attachment between influencers and followers strengthens the effect on willingness to buy an endorsed brand approving moderation (β = 0.584, p < .05). Trust is also an important mediator as it plays a central role between characteristics of social media influencers and intention to buy products (β = 0.411, p < .05). This study discussed the implications and future research directions while incorporating research limitations.  Acknowledgment The authors extend their appreciation to the deanship of scientific research at King Khalid University for funding this work through a large group research project under grant number (RGP. 2/554/45).